Bis-pyrimidine acetamides: design, synthesis and biological evaluation - Kumar, Sanjiv (Chem Cent J, 2017)
BACKGROUND: In the past few years, increased resistance of microorganisms towards antimicrobial agents become a serious health problem, so there is a need for the discovery of new antimicrobial agents. On the other hand, bis-pyrimidines possess various types of biological activity. In view of this, in the present study we have designed and synthesized a new series of bis-pyrimidine acetamides by Claisen–Schmidt condensation and screened for its in vitro antimicrobial and anticancer activities. RESULTS: The synthesized bis-pyrimidine acetamide derivatives were confirmed by IR, (1)H/(13)C-NMR, Mass spectral studies as well C, H, N analyses. The synthesized compounds were evaluated for their in vitro antimicrobial potential against Gram positive (Staphylococcus aureus and Bacillus subtilis); Gram negative (Escherichia coli, Pseudomonas aeruginosa and Salmonella enterica) bacterial and fungal (Candida albicans and Aspergillus niger) strains by tube dilution technique and the minimum inhibitory concentration (MIC) recorded in µmol/mL was comparable to reference drugs, cefadroxil (antibacterial) and fluconazole (antifungal). The in vitro anticancer activity (IC(50) value) determined against human colorectal carcinoma (HCT116) cancer cell line by Sulforhodamine B (SRB) technique and 5-fluorouracil used as reference drug. CONCLUSIONS: The biological study demonstrated that compounds 3, 13, 16, 17 and 18 were found to be most active antimicrobial agents with best MIC values than the cefadroxil (antibacterial) and fluconazole (antifungal) and compounds 12, 16 and 18 found to have better anticancer activity against human colorectal carcinoma (HCT116) cancer cell line with best IC(50) value than the 5-fluorouracil (anticancer). [Figure: see text]